ORGANIZATIONAL AND ECONOMIC MECHANISM OF MIGRATION REGULATION OF WORKING-AGED RURAL POPULATION (ON THE EXAMPLE OF THE SARATOV REGION), RUSSIA - Sergey Germanovich GLUKHOV; Marina Sergeevna YURKOVA; Gennadiy Gennadievich KRYUCHKOV; Nataliya Vladimirovna PROVIDONOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Problems of migration of working-aged countryside population of rural territories are revealed. The organizational and economic mechanism of migration regulation of working-aged country people consisting of 2 modules – organizational and economic is developed and offered. The organizational module includes the directions of reduction of migration due to accounting of the major attracting and repellent factors. A basis of the economic module – fixing of professionals and working-aged population by means of creation of new and additional jobs in the village with using a wide package of measures. Use of the offered mechanism will allow to provide conditions for fixing of working-aged population in rural territories and to reduce migration.